Join the QuestionCove community and study together with friends!
Sign Up
OpenStudy (anonymous):
start with
\[3^2=3^{\frac{1}{2}(4x+6)}\]
OpenStudy (anonymous):
meaning
\[2=2x+6\] and solve for x
OpenStudy (anonymous):
x=3?
OpenStudy (anonymous):
that is not what i get
OpenStudy (anonymous):
can you solve
\[2=2x+6\]? it should take two steps only
Still Need Help?
Join the QuestionCove community and study together with friends!
Sign Up
OpenStudy (anonymous):
-4
OpenStudy (anonymous):
damn i made a mistake hold on
OpenStudy (anonymous):
i mite be wrong
OpenStudy (anonymous):
should be
\[2=2x+3\] so
\[-1=2x\]
\[x=-\frac{1}{2}\]
OpenStudy (anonymous):
can u explain the steps to slove in words
Still Need Help?
Join the QuestionCove community and study together with friends!
Sign Up
OpenStudy (anonymous):
starting where?
OpenStudy (anonymous):
like explain the stretegy used to solve this equation
OpenStudy (anonymous):
if you have
\[9=\sqrt{3}^{4x+6}\] would look to rewrite so the base is the same
OpenStudy (anonymous):
the set up here is
\[9=3^2\] and
\[\sqrt{3}=3^{\frac{1}{2}}\]
OpenStudy (anonymous):
since the bases are now the same, that means the exponents must be the same, so
\[2=\frac{1}{2}(4x+6)\] and now you have a linear equation to solve, which is a whole different problem, although a rather easy one in this case
Still Need Help?
Join the QuestionCove community and study together with friends!
Sign Up
OpenStudy (anonymous):
u can do it all in just words beause part of my assignment is to explain the process in compltet senetnces
OpenStudy (anonymous):
first distribute and get
\[2=2x+3\] then subtract 3 from both sides to get
\[-1=2x\] then divide by 2 and get
\[x=-\frac{1}{2}\]